A study of hydration of cement pastes by reflection of ultrasonic shear waves - Valič, Marko (Kovine zlitine tehnologije, 1998)
In this work an apparatus employing a novel nondestructive method based on the reflection of ultrasonic shear waves is described. Application possibilities for studies of the early hydration process of pastes in selected hydraulic, mostly cementitious materials are presented. The results obtained demonstrate, that the acoustic shear wave metod presented is quite sensitive to different parameters (composition, water/cement ration, fineness, grain size distribution, addition of additives) which influence the hydration process of these materials. Applications to curing process following, in time domain, of non-cement compounds are possible. On the basis of an evaluation of these and other experimental studies a compact 'hardness and cure meter' for industrial testing and for research will be constructed.
Keywords: cement; hidratacija; strjevanje; ultrazvočne preiskave; kemijska kinetika